The Lightning Effects to the Aircraft Front Nose Radome Region - K. Tonmitr, K. Tonmitr; A. Kaewrawang, A. Kaewrawang; A. Suksri, A. Suksri; W. Thanasate-Angkool, W. Thanasate-Angkool (Engineering and Applied Science Research, 2013)
This research is to study the lightning effects on the aircraft nose radome region and determine a suitable ratio of lightning diverter strips (LDS) versus antenna length for the protection of the aircraft front nose radome. An experiment is conducted using reduced scale of an aircraft model with the ratio of 1:40 based on results obtained from experiments, suitable LDS length per antennas with value of greater than 1 will have a capability to protect the nose radome from lightning with appropriate angle of 15-165 degree configuration.